Temporal and spatial variability of S-wave and coda attenuation in the Central Apennines, Italy - Gabrielli, Simona; Akinci, Aybige; Del Pezzo, Edoardo (Frontiers in Earth Science, 2025)
The central Apennines are notoriously subject to important seismic sequences, such as the 2009 and 2016–2017, L’Aquila, Amatrice-Visso-Norcia (AVN) sequences, respectively. Here, we examine the temporal and spatial variation of the S-wave attenuation in Central Italy over a period from 2011 to 2017, including the AVN sequence. First, we computed the S-wave attenuation (Qβ) as a function of frequency Q(f) using the coda normalization method. Then, to visualize the spatial variation of the attenuation over time, we calculated the attenuation of coda waves using a novel 2D kernel-based function over the study area. Our results showed a 13% variation in S-wave attenuation between the pre-sequence (2011–2016) and the sequence phase, with a significant 37% decrease in Q (increase in attenuation) detected during the Visso period. Spatially, a high attenuation anomaly aligns with the Monti Sibillini thrust formation, while in time, we observed a northward migration of this high attenuation during the Norcia phase. Temporal variation in the crustal S-wave attenuation and its frequency dependence may be linked to fluid movement and fracturing developed during the AVN sequence. Coda-Q mapping confirmed an increase in attenuation during the sequence within the fault plane zones. Additionally, the broader area of interest reveals a northward extension of high attenuation, following the NS direction of the Monti Sibillini thrust.